Efektivitas Serbuk Kulit Pisang Nangka (Musa Paradisiacal) dalam Menurunkan Kekeruhan Suhu dan pH Air Sumur Gali - Wahyuningsih, Sarah Sri; Chairani, Miftah; Adiningsih, Ridhayani; Askur, Askur (Jurnal Kesehatan Lingkungan Mapaccing, 2023)
Water sources commonly used by the community include wells. Well water is one of the facilities most commonly used by the community as a source of drinking water and clean water as well as daily needs. Therefore, water used to meet daily needs must meet the requirements regulated in the Republic of Indonesia Minister of Health Regulation NO. 2 of 2023 concerning environmental health quality standards. This research aims to determine the effectiveness of jackfruit banana peel powder in reducing temperature and pH turbidity in dug well water. This research uses an experimental method, namely by conducting trials on research subjects, then the effects of the intervention are measured and analyzed tests were carried out based on variations in dose concentration. Based on the results obtained, reducing turbidity levels in dug well water using jackfruit banana peel powder at a dose of 6 grams was able to reduce turbidity up to 3.07 NTU, at a dose of 7 grams it was able to reduce turbidity to 2.95 NTU and at a dose of 8 gram is able to reduce turbidity by 2.38 NTU. And jackfruit banana peels are made into powder to lower the pH of dug well water. Jackfruit banana peel powder at a dose of 6 grams can lower the pH to 7.4, at a dose of 7 grams it can lower the pH to 7.13 and a dose of 8 grams can lower the pH to 7.13. The conclusion of this research is that the most effective dose in reducing the turbidity of dug well water is 7 grams and the most effective dose in reducing the pH of dug well water is 6 grams. It is hoped that future researchers will use more than one dug well water sample